Ansiedad ante el desempeño musical en estudiantes de música peruanos: diferencias de acuerdo con el género, la institución educativa y el género musical - Chang Arana, Álvaro Mario (2016)
Levels of music performance anxiety (MPA) were compared in a sample of 455 Peruvian music students according to gender (males=337; females=113; missing=5), musical institution (two private and one state) and musical genre. Only gender showed an effect on MPA scores, picturing higher scores for the female group, although cultural variables could account for this difference. There were no effects of educational institution or musical genre as determined on MPA scores.